Aptamer-Functionalized Gold Nanoparticle Assay for Rapid Visual Detection of Norovirus in Stool Samples - Maytawan Thanunchai; Sirikwan Sangboonruang; Natthawat Semakul; Kattareeya Kumthip; Niwat Maneekarn; Khajornsak Tragoolpua (Biosensors, 2025)
Norovirus (NoV), a leading cause of acute gastroenteritis worldwide, imposes significant morbidity and economic burdens across all age groups. Timely and accurate laboratory diagnosis is crucial for effective outbreak control and patient management. However, current diagnostic methods often require specialized equipment, technical expertise, and considerable time. To address these challenges, we developed a visual detection method utilizing gold nanoparticles (AuNPs) functionalized with the SMV25 aptamer specific to the NoV capsid protein. Detection relies on MgCl2-induced changes in the color and absorbance of these aptamer-functionalized AuNPs. The assay exhibited a good linear relationship between the A630/A520 absorbance ratio and NoV capsid protein concentration. Specifically, in a buffer system, this linearity (R2 = 0.9026) was observed over a 0–32 ng/µL range with a limit of detection (LOD) of 9.65 ng/µL. Similarly, for NoV spiked into stool suspensions, a strong linear correlation (R2 = 0.9170) was found across a 0–100 ng/µL range, with an LOD of 37.11 ng/µL. Evaluation with real stool samples yielded 77% sensitivity and 65% specificity. Notably, the assay demonstrated the highest sensitivity towards NoV GII.2 (100%), followed by GII.4 (78%). Scanning transmission electron microscopy confirmed the underlying aggregation and dispersion patterns of the aptamer-functionalized AuNPs. This colorimetric assay provides a simple, rapid, and visual method for NoV detection. Nevertheless, further enhancements are necessary to improve its performance in the direct testing of complex specimens, paving the way for future on-site detection applications, especially in resource-limited settings.